Assessment of thermal comfort of nanosilver-treated functional sportswear fabrics using a dynamic thermal model with human/clothing/environmental factors. Issue 4 (February 2018) - Li, Rui; Yang, Jie; Xiang, Chunhui; Song, Guowen
The development of nanotechnology has made it possible to add desirable functions to fabrics. Nanosilver has been used to provide antibacterial and odor control functions for sportswear over decades. However, few studies have explored the thermal comfort and ultraviolet (UV) protection properties of nanosilver-treated sportswear fabrics. In this study, a dynamic thermal model was introduced to predict the thermal comfort of nanosilver-treated fabrics for wearers in different environmental conditions. Nanosilver was applied to cotton and polyester knit fabrics and their antibacterial and UV protection properties were evaluated as well. The results indicated that substantial antibacterial and UV protection properties were achieved from nanosilver-treated fabrics. The dynamic thermal model predicted the thermal comfort of the treated fabrics for various human, clothing, and environmental factors. Although there was between two and four times difference in the thermal and evaporative resistance between the two tested fabrics, the predicted thermal comfort sensations were not significantly different in the same human and environmental conditions. From these results, it can be concluded that nanosilver-treated fabrics may provide desirable functionality, while not detracting from thermal comfort. This is one of the first trials in which a dynamic numerical thermal model was used to predict the thermal comfort of nanosilver-treated fabrics for sportswear, taking human, clothing, and environmental conditions into consideration.